MORPHOLOGICAL AND MOLECULAR CHARACTERISTICS OF SOME NEMATODE SPECIES OF THE FAMILY PROTOSTRONGYLIDAE LEIPER, 1926 - A. E. Kuchboev; R. R. Karimova; B. N. Ruziev; I. B. Salahutdinov; Sh. Sh. Egamberdiev (Российский паразитологический журнал, 2016)
Objective of research: conducting morphological and molecular-genetic identification and studying phylogenetic relations between protostrongylids. Materials and methods:  helminthological material was  collected from  wild  (Capra sibirica, C. falconeri, Ovis vignei and O. ammon) and domestic hollow horned  ruminants (C. hircus and O. aries), and land mollusks of the family Xeropicta in the piedmont and mountain area of Uzbekisan. The morphology of protostrongylids was studied using the  methods of Boev (1975) and Anderson (1978). To identify the nematode type we used temporary preparations treated with glycerol. The first-stage larvae were investigated by examination of fecal samples from animals taking  into account the length, tail form and body size. To study the morphology of  the third-stage protostrongylid larvae  the feet of infected  mollusks  Xeropicta candaсharica were separated and placed into the artificial gastric juice where the cap was destroyed and the infected larvae were eliminated. After determination of species belonging of mature and larval nematodes the material was stored in separate test-tubes with distilled water under the low temperature (- 20 ºС) or in 70 % Ethanol for the molecular analysis. We used microscopes ML 2000 with a digital camera and Olympus CX3. DNA extraction, amplification and sequencing were performed with an automated sequencer. Phylogenetic analysis was conducted using the software Clustal X 2.0. Phylogenetic trees were created by the Neighbor–Joining method. Nucleotide sequences ITS-2 regions of species Protostrongylus rufescens  (EU018485), P. shiozawai  (AB478249),  Ortostrongylus macrotis  (EU018483),  Cystocaulus ocreatus  (EU018481) and Umingmakstrongylus pallikuukensis  (AY648409) received from the NCBI GenBank  were used in phylogenetic analysis.  Results and discussion:  Four species of adult protostrongylid nematodes: Protostrongylus rufescens, P. hobmaieri, Spiculocaulus leuckarti and Cystocaulus ocreatus were determined. DNA from four species of mature protostrongylids and larvae was amplified  by using  ITS-2 regions. Amplificate dimension of nematodes P. rufescens and P. hobmaieri was 380 base pairs (b.p.), S. leuckarti   – 388, C. ocreatus – 399 b.p. According to the  results of phylogenetic analysis and comparison of nucleotide sequences, five protostrongylid  species were found  in animals of the Caprinae subfamily:  P.  rufescens, P.  hobmaieri, Protostrongylus sp., S.  leuckarti  and  C.  ocreatus.  The morphological and molecular-genetic analysis  of detected nematodes enables the precise identification.